Two Voices of the Spanish Crisis. - Seguín, Bécquer (Boundary 2, 2020)
The article informs about examines intellectual authority and the construction of popular dissent in contemporary Spain. Topics discussed include understanding how intellectual authority has been mobilized and how popular dissent has been harnessed during the Great Recession; collection of manifestos from intellectuals in Spain spanning the entire twentieth century; and software developers in Madrid that has been prominently used by the political party Podemos.